PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI UNTUK MENINGKATKAN KETERAMPILAN LITERASI AWAL ANAK USIA DINI DI KELOMPOK B TK AL-KHAIRAAT PARIGI KABUPATEN PARIGI MOUTONG - Amrullah, Amrullah; Awalunisah, Sita; Imamah, Zakiyyatul (Universitas Hamzanwadi, 2025)
This research aims to examine broadly and in depth the development of technology-based learning programs to improve early childhood literacy. In this context, technology-based learning media includes learning through videos specifically designed to improve early childhood literacy skills. With this research, it is hoped that it can provide a deeper understanding of the potential of technology-based learning media in improving early childhood literacy skills, so researchers are interested in conducting research with the title